Tooth replacement in the non-mammalian cynodont Cynosaurus suppostus (Therapsida) from the late Permian of South Africa. Issue 4 (4th July 2021) - Norton, Luke A.; Abdala, Fernando; Rubidge, Bruce S.; Botha, Jennifer
ABSTRACT: Five specimens of the late Permian cynodont Cynosaurus suppostus, inferred to represent an ontogenetic growth series, were imaged using X-ray microtomography in order to determine the pattern of tooth replacement for the species. Due to the small sample size, and damage to the rostrum in several specimens, replacement patterns of the incisors could not be accurately determined. Evidence supporting the presence of two maxillary canine loci in a juvenile Cynosaurus is presented. Replacement of the mandibular canines ceased at a basal skull length of ∼88 mm, whereas replacement of the maxillary canines ceased at a basal skull length of ∼90 mm. The final canine generation to erupt in both the maxillae and mandible had open-rooted apices. An alternating pattern of replacement is described for the maxillary and mandibular postcanine series. Postcanine replacement generations in the maxilla are seemingly separated by two tooth loci, whereas in the mandible replacement activity occurs at alternating loci. Cessation of replacement in the first maxillary postcanine locus (PC1) is synchronized with the eruption of the replacement tooth in the third locus (PC3). This cessation of replacement at PC1 results in a distal migration of the entire maxillary postcanine series. This pattern provides possible evidence for a finite number of replacement generations occurring at the active PC1. There appear to have been two replacement cycles per postcanine locus in Cynosaurus, which is a lower number of total replacements per postcanine locus than previously estimated for the Early Triassic basal cynodont Thrinaxodon liorhinus .